Effectiveness of E-Learning on Students' Learning Process at Catholic University of Eastern Africa - Ochoo, Olivia Susan; Mwalw'a, Shem; Nduku , Elizabeth (Journal of Education and Practice, 2023)
Purpose: The main aim of this study was to investigate the effectiveness of eLearning on the student's learning process at the Catholic University of Eastern Africa. The research questions addressed the following areas: how students access educational learning resources on e-learning platforms, how eLearning has been integrated into the process of learning, how eLearning integrations affect students' learning process, how computer-based learning influences students'' completion rate at the CUEA, how e-learning and traditional learning environments significantly relate to students' learning process, the challenges that are associated with e-learning, and the mitigation measures the university is taking to resolve the eLearning challenges. Methodology: The researcher used an integrated mixed-method approach involving qualitative and quantitative paradigms. Probability and non-probability sampling techniques were used. The target population for the research was 816 out of which, 260 respondents were sampled. From the sampled population, 218 participated in the research making an 85% return rate. The hypothesis was tested using chi-square, while internal consistency was used to ensure the internal reliability of the research instruments. Cronbach validity was used to validate the Likert scale items. Besides, correlation was used to find out the relationships between the dependent and independent variables. The researcher obtained approval from the faculty of education and permission from NARCOSTI to collect data from the respondents. Findings: The research findings revealed that independent variables, eLearning benefits, eLearning resources, eLearning incentives, and eLearning integration contribute to students' learning process. The research further revealed that the introduction of a favorable and supportive eLearning environment positively influences Students' Learning Processes. The researcher concluded that eLearning contributes to the effective learning process of students, therefore, is imperative to be embraced. Unique Contribution to Theory, Policy and Practice: The researcher recommended that the government, curriculum developers and IHL focus on Instructional design, build a strong Learning management system, guidelines and policy, comparative analysis, leverage Cultural and Global perspectives, eLearning accessibility, engagement, Assessment and evaluation of the eLearning platform. Besides, the students subscribing to the eLearning platform should be given proper orientation in order to navigate the platform easily.